O7 Toll-like receptor 3 mediates osteoblastic phenotype switch in calcific aortic valve disease. (30th July 2021) - Gollmann-Tepeköylü, C; Graber, M; Pölzl, L; Hirsch, J; Nägele, F; Naschberger, A; Kirchmair, E; Degenhart, G; Demetz, E; Lobenwein, D; Lener, D; Fuchs, C; et al.
Abstract: Introduction: Calcific aortic valve disease (CAVD) is caused by an osteoblastic phenotype switch of valvular interstitial cells (VICs), the predominant cell type in heart valves. However, the trigger for the phenotype switch remains unknown. Toll-like receptor 3 (TLR3) is part of the innate immune system activated by viral and endogenous RNA released from injured cells. We hypothesized that mechanical strain leads to TLR3 activation leading to an osteoblastic phenotype switch of VICs with subsequent initiation of CAVD. Methods: Aortic valves were obtained from patients undergoing aortic valve replacement or from explanted hearts. VICs were isolated and treated with TLR3 agonist poly (I: C) or a TLR3/dsRNA complex inhibitor. Osteoblastic gene expression was evaluated via RNA sequencing. Cells were challenged with osteoblastic medium and analyzed for alkaline phosphatase activity and calcific nodule formation. Zebrafish were treated with TLR3/dsRNA complex inhibitor. A Flexcell system was used to apply mechanical strain to VICs. Aortic valve morphology and function of aged wild-type (WT) and TLR3-/- mice were analyzed via transthoracic echocardiography, microCT and histological evaluation. To confirm results in a second model, experiments were repeated in ApoE-/- and ApoE-/-/TLR3-/- mice. Results: Aortic valves and VICs showed abundant TLR3 expression. Mechanical stimulation of VICs resulted in TLR3 activation. Stimulation of TLR3 lead to expression of TNF-a, IL-6, IFN-y, IL-10, Runx2 and BMP2 and, caused a phenotype switch towards osteoblasts as revealed by RNA sequencing and resulted in enhanced calcific nodule production. Mice showed age-dependent TLR3 expression. Aortic valves as well as VICs derived from CAVD patients showed increased TLR3 expression compared to healthy control valves and VICs. TLR3 Inhibition resulted in prevention of osteogenic phenotype switch in conditioned VICs. Zebrafish exhibited decreased calcification after TLR3 inhibition. Aged WT mice showed significantly increased mean gradients and mean velocity in transthoracic echocardiographs. MicroCT and histological analyses revealed thickened valve leaflets and commissural atherosclerotic plaques. These changes were missing completely in age-matched TLR3-/- mice. ApoE-/- mice under high fat diet exhibited clear signs of CAVD with decreased aortic valve opening diameters and increased valve leaflet thickness. However, these findings were completely missing in ApoE-/-/TLR3-/- mice. Conclusion: TLR3 stimulation leads to an osteoblastic phenotype switch of VICs, whereas inhibition of TLR3 prevents from osteoblastic activity. TLR3 expression is increased in aortic valves from CAVD patients. TLR3-/- mice show no phenotype of CAVD. TLR3 could become an effective target for the pharmacological prevention of CAVD.